Pengaruh Konten Iklan Dan Ulasan Terhadap Keputusan Pembelian Di Otobox Indonesia Dengan Kepercayaan Konsumen Sebagai Variabel Intervening - Cahyani, Ika Mei; Kurniawan, Bayu; Gultom, Henry Casandra (CV. ITTC INDONESIA, 2023)
This research was conducted with the aim of identifying how advertising content influences consumer trust. The influence of advertising content on purchasing decisions. The influence of reviews on purchasing decisions. The influence of consumer trust on purchasing decisions. The influence of advertising content on purchasing decisions is mediated by consumer trust and the influence of reviews on purchasing decisions is mediated by consumer trust. The population in this study were all Otobox Indonesia consumers in Semarang, Central Java. The sample in this study was a portion of Otobox Indonesia Semarang consumers taken using a purposive sampling method with a total of 96 consumers. The data analysis technique applied in this research uses quantitative data analysis with the help of the AMOS version 22 application program. The results of the research analysis show that advertising content is proven to have a positive and significant influence on consumer trust values. Reviews are proven to have a positive and significant influence on consumer trust scores. Advertising content is proven to have a positive and significant influence on the value of purchasing decisions. Reviews are proven to have a positive and significant influence on the value of purchasing decisions. Consumer trust has been proven to have a positive and significant influence on the value of purchasing decisions for Otobox Indonesia products. Advertising content that is able to optimally assist producers in introducing products to consumers in a sustainable manner will encourage consumers' sense of trust in the value of responsibility on the part of producers regarding the products they offer. The presence of dominant positive reviews on the products being sold will encourage consumers to have more confidence in the seller's responsible attitude regarding the products they offer.